Antibiotic Susceptibility Pattern of Salmonella Enterica serovars Typhi and Paratyphi A Isolated From Patients Suspected of Enteric Fever (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The study aimed to assess the antibiotic susceptibility profile of Salmonella spp isolated from patients suspected of enteric fever.Methods: This cross-sectional prospective study was carried out from April to June, 2014among 484 patients clinically suspected of enteric fever visiting Bir Hospital, Kathmandu, Nepal. Blood sample collected from each patient was processed for culture in bile broth. Identification of Salmonella spp was done by conventional microbiological techniques including colony characteristics, Gram's staining and biochemical tests. Antibiotic susceptibility testing of identified isolates was done by Kirby-Bauer disk diffusion method following the 2014 CLS I guideline.Results: Out of 484 blood samples, 36 (7.43%) cases showed the growth of Salmonella spp; of which 27 (75%) were Salmonella enterica serovar Typhi (ST) and 9 (25%) were Salmonella enterica Paratyphi A (SPA). Among the Salmonella isolates, 5.55% were multidrug resistant and 41.66% were fluoroquinolone resistant. More than 80% of isolates were sensitive to chloramphenicol, amoxicillin, and cotrimoxazole whereas 58%, 50% and 6% of isolates were sensitive to fluoroquinolone antibiotics i.e. ciprofloxacin, ofloxacin and nalidixic acid respectively. All the isolates were susceptible to ceftazidime. All SPA and 89% of ST were sensitive to azithromycin.Conclusion: Higher percentage of susceptible isolates to chloramphenicol, cotrimoxazole, and amoxicillin suggests the reconsideration of these antibiotics for the treatment of enteric fever. Azithromycin can be considered as drug of choice for the treatment of enteric fever.